The Influence of Marketing Campaigns on Business Sustainability Through Customer Satisfaction at Azka Laundry - Imam Permana; Nandang Nandang; Ismail Yusup (The Future of Education Journal, 2025)
The development of marketing strategies has made marketing campaigns increasingly important in shaping customer perceptions and experiences, which ultimately drive customer satisfaction and influence business sustainability amid intense market competition. Azka Laundry is one of the MSMEs that applies marketing campaigns; however, it has experienced a decline in revenue, prompting the business to implement an additional promotional strategy by distributing free takjil. Therefore, this study aims to analyze the influence of marketing campaigns on business sustainability through customer satisfaction using a descriptive quantitative method with 234 respondents. The data were analyzed using SmartPLS through outer model testing, inner model testing, and hypothesis testing. The results show that marketing campaigns have a significant and positive effect on customer satisfaction and business sustainability. In addition, customer satisfaction significantly and positively mediates the influence of marketing campaigns on business sustainability. These findings indicate that the more effective the marketing campaign strategy implemented, the higher the level of customer satisfaction, which ultimately supports the stability and long-term sustainability of Azka Laundry’s business.